Influência dos porta-enxertos e sistemas de condução na qualidade de pêssegos. - Costa, Vagner Brasil (2007)
In general, the fruit quality of in natura destined-peach needs to be improved specially regarding to sensorial, functional and shelf-life characteristics. Most of these problems are well known to begin since the production period and, tree quality and training system might alter these characteristics. Therefore, this work aimed to evaluate the peach quality cultivars Maciel, Jubileu and Eldorado under different training systems as well as different rootstocks for the scion Granada. The parameters assessed were flesh firmness, total soluble solids, color, acidity, total phenol compounds, antioxidant potential and vitamin C, flavor and yield. In the cv. Granada it was done a harvest per rootstock used, and in the different training systems three harvests were performed. In the training systems, it was observed that leader system provided fruits with positive characteristics to in natura consumption, such as color, vitamin C, etc. Nevertheless, the rootstocks Umezeiro and Granada induced better fruit quality whether grafted under the cultivar Granada.